REPOSISI KEDUDUKAN DAN KEWENANGAN PENYIDIK PEGAWAI NEGERI SIPIL (PPNS) DALAM SISTEM PERADILAN PIDANA INDONESIA [REPOSITION OF POSITION AND AUTHORITY OF PPNS IN THE INDONESIAN CRIMINAL JUSTICE SYSTEM] - Oloan C. H. Marpaung (Lex Prospicit, 2023)
PPNS in its position and authority as the embodiment of law enforcement, it can be seen that there is subordination of other law enforcement sub-systems. The purpose of this paper is to reposition the position and authority of the PPNS in the Criminal Justice System so they are not seen as subordinate and placed as assistants to Police Investigators. The formulation of the problem in this study are the position and authority of PPNS in the Indonesian criminal justice system and legal certainty about the position and authority of PPNS in the criminal justice system in Indonesia. This research is a normative-empirical research conducted by analyzing the implementation of normative legal provisions (laws) with a case study approach, then in analyzing the data using a deductive method, namely drawing conclusions from a problem faced that is specific. The results of this study are that the existence of PPNS is very much needed in conducting investigations due to the complexity of the investigation, the existence of special crimes, and the limitations of Polri investigators. Regarding the implementation of the duties of civil servants so that there is no overlap between Polri investigators and PPNS, the government has set various regulations regarding the mechanism for the appointment and dismissal of PPNS, as well as the implementation of coordination and supervision carried out by Polri investigators against PPNS.Bahasa Abstrak Indonesia: PPNS dalam kedudukan maupun kewenangannya sebagai perwujudan dari penegak hukum, dapat diketahui terjadinya sub-ordinasi atas sub-sistem penegak hukum yang lain. Tujuan dari penulisan ini adalah menempatkan kembali (reposisi) kedudukan dan kewenangan PPNS dalam Sistem Peradilan Pidana sehingga tidak terlihat sebagai subordinasi dan ditempatkan sebagai pembantu Penyidik Kepolisian. Rumusan masalah dalam penelitian mengangkat hal kedudukan dan kewenangan PPNS dalam sistem peradilan pidana Indonesia dan kepastian hukum terhadap kedudukan dan kewenangan PPNS dalam sistem peradilan pidana di Indonesia. Penelitian ini adalah penelitian Normatif-Empiris yang dilakukan dengan menganalisis implementasi ketentuan hukum normatif (undang-undang) dengan pendekatan Pendekatan terhadap kasus hukum (case study), kemudian dalam penganalisian data menggunakan metode deduktif, yakni menarik kesimpulan dari suatu permasalahan yang dihadapi yang bersifat khusus.Hasil penelitian ini adalah keberadaan PPNS sangat dibutuhkan dalam melakukan penyidikan dikarenakan kompleksnya penyidikan, adanya tindak pidana yang bersifat khusus, dan keterbatasan dari Penyidik Polri. Terkait pelaksanaan tugas PNS agar harmonis dan tidak terjadi tumpang tindih antara Penyidik Polri dan PPNS, pemerintah telah menetapkan berbagai peraturan mengenai mekanisme pengangkatan dan pemberhentian PPNS, serta pelaksanaan koordinasi dan pengawasan yang dilakukan Penyidik Polri terhadap PPNS.